Comparison of Health Education Technique on the Abortion Knowledge Levels in Students of UNKLAB Airmadidi High School - Korengkeng, Loura Caroline; Tumundoh, Beverly (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Abortion is one of the deviant behavior, and it is also the release of conception before twenty weeks' gestation or a fetus weighing less than five hundred grams. To avoid this deviant behavior, teenagers need information about the dangers and negative effects of abortion. Therefore, health education was given as an important way to increase the knowledge about abortion and its relation to reproductive health. The purpose of this research was to find out which health education techniques were more effective on the level of abortion knowledge in students at UNKLAB Airmadidi High School. This is quantitative research with Quasi Experiment Design with a Pretest-Posttest Nonequivalent Control Group approach. The sample was all 12th-grade students of UNKLAB Airmadidi High School, and data were collected using a questionnaire to measure the level of knowledge. The results from the Independent t-test show the p value= 0,002, which means there was significant relation of health education on the knowledge level of abortion in students at UNKLAB Airmadidi High School. This research recommended that schools must work together with the local health office or public health center to provide health education about adolescent reproductive health. The recommendation for the next researcher is to try different health education techniques, such as video. Keywords : Abortion knowledge, health education, high school